Explore the desert - Jackson, Kay, 1959- (Mankato, Minnesota : Capstone Press, 2007)
Photographs and simple text describes the plants, animals, and characteristics of the desert biome.
3-6
810L
Q
Center for the Collaborative Classroom Curriculum.
Keywords: Desert ecology; Ecology